Case report: Clinical analysis and literature review of five cases of metastatic solid pseudopapillary tumor of the pancreas - Hu, Run; Gui, Renjie; Nie, Xi; Duan, Huaxin (Frontiers in Oncology, 2024)
BackgroundSolid pseudopapillary neoplasm of the pancreas (SPN) is a rare and low-grade malignant tumor. It mainly occurs in women of reproductive age, accounting for approximately 1-3% of all pancreatic tumors. SPN has a low incidence rate and is difficult to diagnose before surgery. Some cases may show local infiltration, but distant metastasis rarely occurs. Currently, there is no standardized treatment protocol for SPN.Patient and methodsWe have collected clinical data from 5 patients with solid pseudopapillary neoplasm (SPN) of the pancreas who presented with distant metastasis at our hospital. This study retrospectively analyzes their clinical manifestations, imaging characteristics, pathological findings, and treatment outcomes. The aim is to summarize the clinical features of SPN with distant metastasis, thereby improving the diagnosis, treatment, and prognosis prediction of this disease. This study also reviews relevant literature.ResultsThe median age of the 5 patients was 32 years old, with a male-to-female ratio of 1:4. All patients underwent enhanced CT scans and were diagnosed with SPN through biopsy or surgical pathology. All 5 patients had liver metastases, and one patient had clavicular lymph node metastasis. Another patient had both lung and clavicular lymph node metastases. Three patients underwent curative surgery, one patient received chemotherapy combined with targeted immunotherapy and subsequently underwent TACE(Transcatheter arterial chemoembolization) and HAIC (Hepatic artery infusion chemotherapy) treatments due to progression. One patient received internal radiation therapy but experienced multiple relapses and eventually died due to complications. The follow-up period ranged from 7 to 53 months, with 2 patients succumbing to the disease.ConclusionAs a low-grade tumor, SPN has a low rate of distant metastasis, typically occurring in only 5%-15% of cases. These metastases often lack characteristic clinical symptoms. Diagnosis can only be confirmed after exclusion of other lesions through imaging and pathological examination. The primary treatment for metastatic SPN is curative surgery, which can lead to a favorable prognosis.